Endovenous Laser Application - Sroka, R.; Pongratz, T.; Siegrist, K.; Burgmeier, C.; Barth, H.-D.; Schmedt, C.-G. (Phlebologie, 2013)
Introduction: Endoluminal vein treatment is a promising minimal invasive treatment option for peoples suffering from varicose veins. The basic mechanism underlying this procedure is to selectively induce heat in the vessel wall with the result of denaturation of proteins and shrinkage of collagen fibers due to energy application. So far energy could be applied either as RF-current, laser light or water steam. The different approaches to deliver such forms of energies are described.Methods: Investigations on heat dependent vein tissue effects were performed. The degree of shrinkage and wall thickening due to heat induction was calculated. Tensile test on vein tissue were performed. Investigation using the radial emitting laser fibre in the ox-foot-model under reproducible condition were done and wavelengths dependent tissue reaction were explored.Results: The experiments clearly demonstrate the degree of the shrinkage of length and diameter, the thickening of the vein wall, as well as the decrease of the elasticity of the tissue. The optical irradiation pattern of the radial emitting laser fiber serves for safe and reproducible energy application directly to the vein wall. Using a laser wavelength with high absorption by the tissue water needs reduced irradiation and irradiance compared to wavelengths with less water absorption. Conclusion: An experimental approach to improve laser application for endovenous varicose treatment is described. Laser parameters and treatment parameters were found which are now under clinical testing. The demonstrated tissue effects may help to find further arguments for clinical findings and sensations described by the patients during follow-up.
Keywords: Varicosis; laser; radiofrequency; fibre